Impact of the Domestic Violence Housing First Model on Survivors’ Safety and Housing Stability: 12-Month Findings - Sullivan, Cris M. (Journal of interpersonal violence, 2023)
Intimate partner violence (IPV) is a widespread and devastating phenomenon resulting in a myriad of long-term consequences for survivors and their children. IPV victimization not only has negative health and economic consequences, it has also been linked to homelessness and housing instability. In response, the Domestic Violence Housing First (DVHF) model is being used in some domestic violence (DV) agencies to help survivors attain safe and stable housing. The model includes using individualized advocacy and/or flexible funding to help survivors meet these goals. Using a longitudinal, quasi-experimental design, the current study involved conducting interviews with survivors and examining agency records to investigate the effectiveness of this model. We hypothesized that survivors who received DVHF would experience less re-abuse and greater housing stability over 12 months compared to those who received services as usual (SAU). The sample included 345 IPV survivors who had been homeless or unstably housed when they approached one of five DV programs for help. Interviews were spaced 6 months apart (when survivors first sought services as well as 6 months and 12 months later). Longitudinal analyses showed that survivors who received the DVHF model reported greater improvements in housing stability at both the 6-month and 12-month time points compared to those receiving SAU. At the 12-month time point, survivors who had received DVHF reported decreased physical, psychological, and economic abuse, as well as the use of their children against them as a form of abuse. This study adds to a growing body of evidence supporting this model’s effectiveness and adds to our understanding of factors impacting the long-term housing stability and safety for IPV survivors.